KONFLIK PEMANFAATAN SUMBER DAYA AIR UNTUK IRIGASI SAWAH DAN KOLAM DI KECAMATAN MAOS, KABUPATEN CILACAP - Murni Handayani; Rosita Dwityaningsih; Nurlinda Ayu Triwuri (Yayasan Akrab Pekanbaru, 2018)
Wetland farmers in Maos District, Cilacap Regency were originally all farmers of paddy fields, but the increasing economic need, the farmers began to shift to fish farmes (pond) because the income is hgher. However, this resulted in conflicts over the utilization of water resources for paddy fields and ponds. The research method is deskriptive, databased on interview result both to farmer of paddy field, pond farmer, water user officer and related service in Maos District, Cilacap Regency. The result showed that conflict of utilization of water resources of irrigation in Maos District between wetland farmer and fish farmer (pond) have an effect on paddy farmer production result. Rice production is not optimal because water that should be used for irrigation is reduced to the pond. Maintained capacity of the irrigation network can ensure the water requirements of farmers. The Goverment as a main authorities in management of primary irrigation network, needs to improve its capabilities especially in allocating operational and maintenance funds. To increase paddy production and the welfare of society, policies need to be done first is to increase the irrigation capacity. Keywords : conflict, paddy field, fish pond